2016
DOI: 10.1186/s40364-016-0067-2
|View full text |Cite
|
Sign up to set email alerts
|

The CXCR4 antagonist plerixafor enhances the effect of rituximab in diffuse large B-cell lymphoma cell lines

Abstract: BackgroundDiffuse large B-cell lymphoma (DLBCL) is an aggressive disease with variable clinical outcome, accounting for at least 25-30 % of adult non-Hodgkin lymphomas. Approximately one third of DLBCL patients are not cured by the currently used treatment regimen, R-CHOP. Hence, new treatment strategies are needed. Antagonizing the CXCR4 receptor might be promising since the CXCR4-CXCL12 axis is implicated in several aspects of tumor pathogenesis as well as in protection from chemotherapeutic response. In Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…To our knowledge, this is the first evidence of plerixafor affecting miR‐9‐mediated cellular functions. Usage of plerixafor has shown dramatic reduction in carcinogenic phenotype induced by CXCR4 in various in vitro cancer studies in solid tumours such as prostate and cervical cancers (Chaudary et al ., ; Conley‐LaComb et al ., ), as well as lymphomas (Reinholdt et al ., ). Plerixafor is already approved for the mobilisation of hematopoietic stem cells in lymphoma and multiple myeloma patients (Wagstaff, ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first evidence of plerixafor affecting miR‐9‐mediated cellular functions. Usage of plerixafor has shown dramatic reduction in carcinogenic phenotype induced by CXCR4 in various in vitro cancer studies in solid tumours such as prostate and cervical cancers (Chaudary et al ., ; Conley‐LaComb et al ., ), as well as lymphomas (Reinholdt et al ., ). Plerixafor is already approved for the mobilisation of hematopoietic stem cells in lymphoma and multiple myeloma patients (Wagstaff, ).…”
Section: Discussionmentioning
confidence: 99%
“…Peled et al demonstrated that disrupting the CXCL12/CXCR4 axis using motixafortide is an effective way to abrogate the BM-derived mesenchymal stem-cell-mediated resistance of nHL cells to rituximab and to target nHL in the BM microenvironment [139]. Furthermore, plerixafor can enhance the effect of rituximab in DLBCL cell lines in vitro [140]. Previous studies have confirmed that abnormal activation of the PI3K/AKT/mTOR signaling pathway increases tumor proliferation and is associated with the poorer prognosis of patients with DLBCL [141].…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…[7][8][9] Thus, the CXCR4-CXCL12 axis is involved in tumor pathogenesis, cancer cell survival, stem cell phenotype, and resistance to chemotherapy. 10,11 In addition, CXCR4 is constitutively over-expressed in NHL cell lines, 12,13 and also in approximately 50% of malignant B-cell lymphocytes derived from DLBCL patients. 8 Interestingly, CXCR4 + DLBCL cell lines show resistance to rituximab but are sensitive to the combination of rituximab with a CXCR4 antagonist.…”
Section: Ferrata Storti Foundationmentioning
confidence: 99%